Kualitas Fisik, Mikrobiologis, dan Organoleptik Telur Konsumsi yang Beredar di Sekitar Kampus IPB, Darmaga, Bogor - Suharyanto, Suharyanto; Sulaiman, N. B.; Zebua, C. K. N.; Arief, I. I. (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2016)
This study was conducted to evaluate physical, microbiological, and organoleptic quality of layer eggs marketed around IPB campus Darmaga, Bogor. Egg samples were obtained from three market groups (supermarket, retailer, and traditional market). Each group includes three markets determined purposively, namely SM-1, SM-2, and SM-3 for supermarkets; BR-1, BR-2, and BR-3 for retailers; and TM-1, TM-2, and TM-3 for traditional markets. Physical qualities measured were egg weight, yolk index, albumen index, air sac height, pH and Aw. Microbiological quality was expressed as colony forming unit with Total Plate Count (TPC) method and the number of Escherichia coli colony formed. Organoleptic properties evaluated were hedonic and hedonic ranking test. All physical and microbiological qualities of eggs showed no significant differences among markets origin. This study confirmed that eggs excluded from SNI 3926-2008 (Indonesia National Standard for consumption egg) and other scientific findings. However, the low physical and microbiological qualities did not cause any refusing on the acceptability of sensorial properties by panelists.